Isomerization of 6-O-substituted glucose and fructose under neutral pH conditions and subsequent β-elimination reactions. (September 2022) - Chiku, Kazuhiro; Ohfuji, Ayaka; Ohtake, Nozomi; Yoshida, Mitsuru; Ono, Hiroshi; Kitaoka, Motomitsu
Abstract: Isomaltose (6- O -α-d -glucopyranosyl-d -glucose) and isomaltulose (palatinose; 6- O -β-d -glucopyranosyl-d -fructose) were heated to 90 °C in 100 mM sodium phosphate buffer (pH 7.5). Aldose–ketose isomerization between isomaltose, isomaltulose, and epi-isomaltulose was observed in the early stage of the reaction, alongside the release of a small amount of glucose. The total concentration of these disaccharides gradually decreased as the heating time increased. However, this decrease did not correlate with the amount of glucose or fructose released, suggesting that the releases of these monosaccharides were not caused by the hydrolysis of glycosidic linkages. A slight decrease in the pH of the reaction solution was attributed to the formation of two organic acids, 6- O -β-d -glucopyranosyl-3-deoxy-d - arabino -hexonic acid (1 ) and 6- O -β-d -glucopyranosyl-3-deoxy-d - ribo -hexonic acid (2 ). These compounds were formed from the β-elimination of the hydroxyl group at the C-3 of fructose, leaving a substituted glucose residue at the C-6 position, followed by keto–enol tautomerization and benzilic acid rearrangement. Although approximately 30% of 1 and 2 were degraded after 360 min of heating at 90 °C in 100 mM sodium phosphate, a little release of glucose was observed, indicating no hydrolysis of the glucoside bond at C-6. Besides 1 and 2, time-dependent changes in the NMR spectra of the reaction mixture in water indicated the formation of formic acid and the presence of species possibly resulting from the β-elimination of the hydroxyl group from 3- and 4-ulose. The glucose released by heating isomaltose and isomaltulose may be generated via tautomerizations of keto-enols between the C-4 and C-5 positions and cleavage of 6- O -glycosidic linkage via β-elimination. Graphical abstract: Image 1 Highlights: Aldose–ketose isomerization occurred upon heating isomaltose at neutral pH. 6- O -β-d -Glucopyranosyl-3-deoxyhexonic acids were formed after long-term incubation. The reaction mechanism involved aldose–ketose isomerization and β-elimination. Glucose release was not triggered by hydrolysis but by an elimination reaction. The glycosidic bond elimination reaction can be extended to 6- O -substituted hexoses.